Woman's Position And Role In Arthur Golden's Memoirs Of A Geisha : A Feminist Approach - Amarwati, Indri Wahyu (2005)
The major problem of this study is to reveal how women's position and role are reflected in Arthur Golden's Memoirs of a Geisha. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on the feminist analysis. In analyzing Memoirs of a Geisha, the writer uses qualitative method and feminist approach. The object of the study is Arthur Golden's Memoirs Of a Geisha published in 1997 by Vintage Books, a division of Random House,Inc.,New York. The data sources consist of primary data and secondary data sources. The primary data source is the novel Memoirs of a Geisha itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and feminism. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study shows in the following conclusion. First, in this novel, Arthur Golden wants to illustrate how women are subordinated and exploited in patriarchal society. Second, in this novel, Arthur Golden wants to say that women Right are not given but must be struggled for. Third, in this novel, Arthur Golden wants to describe that in order to get their rights as human beings women should be smart and talented. And the last, this novel contains many facts that are revealed by Arthur Golden which reflect woman's position, woman's role, woman's right, and woman's participation in leading her life as a geisha, and there are also many forms of subordination, oppression, exploitation, and violence toward woman.